Prediction equations of metabolizable energy content in beef cattle diets - Thiputen, Suwit; Sommart, Kritapon (Asia-Pacific Journal of Science and Technology, 2017)
The aim of this experiment was to establish prediction equation for metabolizable energy value of beef cattle feedstuffs. A database was derived from chemical composition, in vitro gas production, dry matter and organic matter digestibility of 6 feedstuffs namely cassava pulp, cassava chip, brewery wasted, coconut meal, and Pangola grass hay. The results suggested that there were twelve suitable prediction equations. Five simple regression equations had coefficient of determination (R2) range from 0.57 to 0.87 and residual standard deviation (RSD) from 0.12 to 0.19 (P<0.001, n = 48). Seven multiple regression equations had R2 ranged from 0.83 to 0.98 and RSD ranged from 0.08 to 0.19 (P<0.001, n = 48). Accuracy and precision of equations evaluated by Paired t-test between actual and predicted value were not significant (P>0.05).The mean proportional bias (MPB) ranged from - 1.27% to 0.01% and mean prediction error (MPE) ranged from 0.039 to 0.174. The Results indicated that the obtained equations had adequate accuracy and precision for prediction the ME value of beef cattle feedstuffs in Thailand. The recommended equations are: ME (MJ/kgDM) = 5.1194 + 0.0845IVOMD24h (R2 = 0.84, RSD = 0.13, n = 48, P<0.001) and ME (MJ/kgDM) = 8.4967 + 0.2944IVDMD24h – 0.2099IVOMD24h – 0.0555NFE (R2 = 0.96, RSD = 0.09, n = 48, P<0.001).